2019
DOI: 10.1177/1420326x19887486
|View full text |Cite
|
Sign up to set email alerts
|

Role of passive design and alternative energy in building energy optimization

Abstract: Energy consumption in buildings can be reduced by employing passive design strategies and with the use of alternative energy resources mainly solar photovoltaic and solar thermal. These measures not only help in reducing the energy bills but also help in mitigating climate change efforts. An optimal solution was obtained by the employment of these measures along with the use of building optimization techniques. Heating, ventilating and air conditioning applications are the conventional means for provision of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The reductions were 39.5, 33.7, 35, 32.7 and 22.7% for the buildings located in Riyadh, Jeddah, Dhahran, Tabuk and Abha, respectively. A study (Gondal et al, 2019) conducted to improve the energy efficiency of the buildings by employing passive design strategies and alternative energy resources. MATLAB and TOPSIS software have been employed for this optimization.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The reductions were 39.5, 33.7, 35, 32.7 and 22.7% for the buildings located in Riyadh, Jeddah, Dhahran, Tabuk and Abha, respectively. A study (Gondal et al, 2019) conducted to improve the energy efficiency of the buildings by employing passive design strategies and alternative energy resources. MATLAB and TOPSIS software have been employed for this optimization.…”
Section: Previous Studiesmentioning
confidence: 99%
“…[1][2][3] Factors affecting terminal energy consumption of public buildings can be categorized into different types in accordance with their building functions. According to previous publications, [4][5][6][7] four types of factors are classified as follows: (1) Meteorological parameters: outdoor dry bulb temperature, solar radiation and wind speed; (2) interior information: occupancy number, power density of lighting and equipment; (3) building schedule: building operating schedule; and (4) basic building information: years of usage, floor area, height, number of stories, building structure, external wall material, external window type and form of air conditioning terminals.…”
Section: Introductionmentioning
confidence: 96%
“…1 Preparation of traditional building materials such as cement, steel and concrete accounts for a large proportion of construction energy consumption. Studies have shown that certain passive measures 2 and renewable building materials 3 in the construction of the building envelope can help reduce the overall energy consumption of the building without compromising the occupants' comfort level. Rammed-earth materials provide good heat storage and humidity control, can be used locally, can be recycled and reused without industrial treatment, and are ecologically sustainable.…”
Section: Introductionmentioning
confidence: 99%